Intercâmbio Cultural na Aldeia Negarotê - Gomides , Adeuza Pereira; Bernhardt , Cristiane Otilia Colossi; Porto, Delma Rodrigues; Minotti, Fabielle Ferreira da Silva; Reis, Geissyane Aparecida Oliveira dos (REVISTA PROGRAMA A UNIÃO FAZ A VIDA_____________________________________________________________________________________________________________, 2021)
>>> ver pdf